Study of a Solar Cells Chimney Wall with House Model Under Hot Humid Climate of Bangkok - จันทวงษ์ ปรีดา; อึ่งกูล โยธิน; ทรัพย์ถาวร วราวุธ; ไมตรีจิตร ชิตพล; แสงอาทิตย์ ธนาทร (Journal of Energy and Environment Technology of Graduate School Siam Technology College, 2014)
This paper reports experimental performance of a Solar Cells Chimney Wall (SCCW) with house model under hot humid climate of Thailand for reducing heat gain and increasing ventilation rate inside houses. The SCCW is composed of a Solar Cells panel, air gap and an inner wall made from autoclaved aerated concrete pane. Its dimensions were 1.50 m height and 0.70 m width. The thickness of the external PV panel and internal concrete wall was about 0.03 m. The SCCW gap was 0.04 m; the size of opening located at the bottom (room side), for increasing ventilation was installed in 0.24 x 0.12 m2, On the top of Solar Cells panel for insect protection was installed in 0.24 x 0.12 m2 opening to exhaust hot air to ambient. The SCCW was integrated into the south façade of a small house 4.05 m3 volume made from autoclaved aerated concrete the thickness 10 cm. Comparison between SCCW and simple concrete wall (SW) using another small house model of the same dimensions was also studied. The experimental results revealed that indoor temperature of SCCW room was lower than that of the single concrete wall room. SCCW induced ventilation rate varied following the intensity of solar radiation. This ventilation reduced heat gain admitted through the south wall considerably.